(E)‐1, 2‐Bis(3, 5‐dinitro‐1H‐pyrazol‐4‐yl)diazene – Its 3D Potassium Metal–Organic Framework and Organic Salts with Super‐Heat‐Resistant Properties. Issue 22 (12th June 2017) - Zhang, Man; Fu, Wei; Li, Chuan; Gao, Huiqi; Tang, Liwei; Zhou, Zhiming
Abstract : ( E )‐1, 2‐Bis(3, 5‐dinitro‐1 H ‐pyrazol‐4‐yl)diazene (H2 NPA, 1 ) and its energetic salts, which are a series of new, energetic, highly heat‐resistant, dense explosives, were synthesized. The explosives contain four nitro groups and an azo‐bridged framework and were characterized by 1 H and 13 C NMR (in some cases 15 N NMR) spectroscopy, IR spectroscopy, and elemental analysis. The crystal structures of K2 NPA (a three‐dimensional metal–organic framework, 3D MOF) and the guanidinium salt4 were determined by single‐crystal X‐ray diffraction, and their properties (density, thermal stability, and sensitivity towards impact and friction) were investigated. The detonation properties were evaluated from the measured density and calculated heat of formation by the EXPLO5 v6.01 program. All of the salts exhibit thermal stabilities with decomposition temperatures ranging from 156 to 315 °C, high densities (1.70–2.15 g cm –3 ), high detonation velocities (8224–9083 m s –1 ), and high positive heats of formation (45.7–1040.1 kJ mol –1 ). The obtained 3D metal–organic framework explosive K2 NPA combines exceptional thermal stability ( T d = 315 °C) with a high density ( d = 2.15 g cm –3 ) and possesses ideal calculated detonation velocity ( v D = 8275 m s –1 ) and pressure ( P CJ = 31.1 GPa) values. Moreover, its suitable impact sensitivity (IS) of 1.5 J and friction sensitivity (FS) of 60 N make K2 NPA an outstanding, highly heat‐resistant, green primary explosive. The guanidinium salt4 also exhibits a high thermal stability ( T d = 304 °C) that is superior to that of HMX, insensitivity to impact (IS > 40 J) and friction (FS > 360 N) comparable to those of 1, 3, 5‐triamino‐2, 4, 6‐trinitrobenzene (TATB), and a high detonation performance ( v D = 8391 m s –1 ). Abstract : Potassium ( E )‐1, 2‐bis(3, 5‐dinitro‐1 H ‐pyrazol‐4‐yl)diazene (K2 NPA), which is a new, energetic, highly heat‐resistant, dense explosive, is synthesized through the straightforward diazotization of 4‐amino‐3, 5‐dinitropyrazole (LLM‐116).